Impact simulation and optimisation of elastic fuel tanks reinforced with exoskeleton for aerospace applications - Prus, C.; Vinuesa, Ricardo; Schlatter, Philipp; Tembras, E.; Mestres, E.; Ramirez, J. P. Berro (International Journal of Crashworthiness, 2017)
The main subject of the study is the impact simulation of an elastic fuel tank reinforced with a polymer exoskeleton. Thanks to its lightweight and failure resistance, this type of design shows potential to be used in aerospace applications. The simulation emulates a drop test from the height of 20 m on a rigid surface, in accordance with Military Handbook testing guidelines for fuel tanks. The focus is on providing an example of modelling and solving this type of problems. The computational methods are tested on a generic model of a rectangular prismatic tank with rounded edges. The walls of the tank are made of orthotropic fabric reinforced polymer. The simulation is performed for a 70% and a 100% water-filled tank. All calculations are performed using the Altair HyperWorks 13.0 software suite, in particular, the nonlinear RADIOSS solver and OptiStruct Solver and Optimiser. The fluid inside the tank is modelled using the SPH (Smoothed Particle Hydrodynamics) approach. The model serves as a basis for establishing a design optimisation procedure, aiming at reduction of mass of the tank components while ensuring structural integrity. The main insights of the current study are the successful modelling of the liquid and the air inside the tank by means of smoothed-particle hydrodynamics elements, and the structural optimisation methodology of a composite fuel tank.
CRIS-Team Scopus Importer:2023-03-21
Keywords: fluid–structure interaction; fuel tank; Impact simulation; SPH; structural optimisation